Self-Management Support Needs of Patients with Chronic Diseases in a South African Township: A Qualitative Study. Issue 1 (2nd January 2017) - Dube, Loveness; Rendall-Mkosi, Kirstie; Van den Broucke, Stephan; Bergh, Anne-Marie; Mafutha, Nokuthula G.
ABSTRACT: Despite the need for chronic disease self-management strategies in developing countries, few studies have aimed to contextually adapt programs; yet culture has a direct impact on the way people view themselves and their environment. This study aimed to explore the knowledge, attitudes, and self-management needs and practices of patients with chronic diseases. Four patient focus groups ( n = 32), 2 patient interviews, group observations, and key informant interviews ( n = 12) were conducted. Five themes emerged: health-system and service-provision challenges, healthcare provider attitudes and behavior, adherence challenges related to medication and lifestyle changes, patients' personal and clinic experiences and self-management tool preferences. The findings provide a window of opportunity for the development of contextually adapted self-management programs for community health nursing in developing countries.